Organising polypharmacy: unpacking medicines, unpacking meanings—an ethnographic study - Deborah Swinglehurst; Nina Fudge (BMJ Open)
Objectives We explore how older patients affected by polypharmacy manage the ‘hidden work’ of organising their medicines, how they make sense of this work and integrate it into their lives.Design and setting Ethnographic study observing patients over 18–24 months in patients’ homes, general practice and community pharmacy, in England, UK.Participants and methods Ethnographic case study including longitudinal follow-up of 24 patients aged 65 or older and prescribed ten or more items of medication. Our dataset includes: 562 hours of ethnographic observation across patients homes, community pharmacies and general practices; 47 audio-recorded interviews with patients about their lives and medicines practices; cultural probes (photographs, body maps, diaries and imagined ‘wishful thinking’ conversations); fieldnotes from regular home visits; telephone calls, and observation/video-recording of healthcare encounters. We apply a ‘practice theory’ lens to our analysis, illuminating what is being accomplished, why and by whom.Results All patients had developed strategies and routines for organising medicines into their lives, negotiating medicine taking to enable acceptable adherence and make their medicines manageable. Strategies adopted by patients often involved the use of ‘do-it-yourself’ dosette boxes. This required careful ‘organising’ work similar to that done by pharmacy staff preparing multicompartment compliance aids (MCCAs). Patients incorporated a range of approaches to manage supplies and flex their regimens to align with personal values and priorities. Practices of organising medicines are effortful, creative and often highly collaborative. Patients strive for adherence, but their organisational efforts privilege ‘living with medicines’ over taking medicines strictly ‘as prescribed’.Conclusions Polypharmacy demands careful organising. The burden of organising polypharmacy always falls somewhere, whether undertaken by pharmacists as they prepare MCCAs or by patients at home. Greater appreciation among prescribers of the nature and complexity of this work may provide a useful point of departure for tackling the key issue that sustains it: polypharmacy.